Bifuran-bridged bisboranes: highly luminescent B-doped oligohetarenes. (2nd October 2020) - Riensch, Nicolas Alexander; Fest, Maximilian; Fritze, Lars; Helbig, Andreas; Krummenacher, Ivo; Braunschweig, Holger; Helten, Holger
Abstract : Boron-doping of oligohetarenes – via classical metathesis or silicon/boron exchange routes – led to strongly luminescent and twofold reversibly reducible oligomers. Abstract : A series of bifuran-bridged bis(triarylboranes) have been synthesized via classical metathesis or catalytic silicon/boron exchange reactions, respectively. The products obtained are strongly luminescent, with quantum yields up to 85%, and reversibly twofold reduced via successive one-electron processes.